2019
DOI: 10.1016/j.schres.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using a smartphone app to assess early signs, basic symptoms and psychotic symptoms over six months: A preliminary report

Abstract: Background Psychosis relapses are common, have profound adverse consequences for patients, and are costly to health services. ‘Early signs’ have been used to predict relapse, in the hope of prevention or mitigation, with moderate sensitivity and specificity. We investigated the feasibility and validity of adding ‘basic symptoms’ to conventional early signs and monitoring these using a smartphone app. Methods Individuals ( n = 18) experiencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 65 publications
2
51
1
Order By: Relevance
“…Additionally, a study that investigated the feasibility of using a smartphone app to assess schizophrenia prompted patients via text message to complete personalized questionnaires once per week. They found that participants (n=18) completed 65% of app assessments, "with 78% completing ≥ 33% app assessments and 72% completing ≥ 50% app assessments" (Eisner et al, 2019), similar to the results observed in this study. In summary, response rates observed in our study were reasonable in the context of previous reports and engagement persisted fairly stably beyond two weeks, demonstrating the application was able to retain patients at least as or more consistently than were applications in previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, a study that investigated the feasibility of using a smartphone app to assess schizophrenia prompted patients via text message to complete personalized questionnaires once per week. They found that participants (n=18) completed 65% of app assessments, "with 78% completing ≥ 33% app assessments and 72% completing ≥ 50% app assessments" (Eisner et al, 2019), similar to the results observed in this study. In summary, response rates observed in our study were reasonable in the context of previous reports and engagement persisted fairly stably beyond two weeks, demonstrating the application was able to retain patients at least as or more consistently than were applications in previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…For example, newly-developed methods for allowing patients to monitor life events by the use of smartphone apps could be beneficial in targeting relapse. Smartphone apps are emerging as a method to monitor psychosis symptoms as relapse predictors (Eisner et al, 2019). A future target of these smartphone apps could be the addition of life event monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…First, when participants inputted information (e.g., rating symptoms and mood), it was perceived to promote greater awareness of current emotional and behavioral patterns. Numerous studies have found that people completing self-monitoring can enhance their understanding of mental health difficulties (Berry et al, 2019; Bucci, Schwannauer, & Berry, 2019; Eisner et al, 2019). Second, participants described an experience of enhanced reflection when therapists’ accessed data inputted into the solution during therapy sessions.…”
Section: Discussionmentioning
confidence: 99%